Target - specificity in scorpions; comparing lethality of scorpion venoms across arthropods and vertebrates (2017)
ABSTRACT: Scorpions use their venom in defensive situations as well as for subduing prey. Since some species of scorpion use their venom more in defensive situations than others, this may have led to selection for differences in effectiveness in defensive situations. Here, we compared the LD50 of the venom of 10 species of scorpions on five different species of target organisms; two insects and three vertebrates. We found little correlation between the target species in the efficacy of the different scorpion venoms. Only the two insects showed a positive correlation, indicating that they responded similarly to the panel of scorpion venoms. We discuss the lack of positive correlation between the vertebrate target species in the light of their evolution and development. When comparing the responses of the target systems to individual scorpion venoms pairwise, we found that closely related scorpion species tend to elicit a similar response pattern across the target species. This was further reflected in a significant phylogenetic signal across the scorpion phylogeny for the LD50 in mice and in zebrafish. We also provide the first mouse LD50 value for Grosphus grandidieri.